Wheel of fortune : the battle for oil and power in Russia - Gustafson, Thane (Belknap Press of Harvard University Press, 2012)
The Russian oil industry is facing mounting problems that could send shock waves through the Russian economy and worldwide. This book provides an authoritative account of this vital industry from the last years of communism to its uncertain future. Tracking the interdependence among Russia's oil industry, politics, and economy, the author shows how the stakes extend beyond international energy security to include the potential threat of a destabilized Russia. The author draws on interviews with key players over the course of two decades to provide a detailed history of the oil industry's evolution since the breakup of the Soviet Union. At its center is the complex and fraught relationship between the oil industry and the state, which loosened its grip under Yeltsin only to tighten it again under Putin. As oil becomes harder to find and more expensive to produce and deliver, Russia's growing dependence on revenue from oil exports, along with its inefficient and often-corrupt management of the industry, is unsustainable.